Early age shrinkage strains at various depths of mortar prism specimens - Ong, K.C.G. (2014)
Creep, Shrinkage and Durability Mechanics of Concrete and Concrete Structures - Proceedings of the 8th Int. Conference on Creep, Shrinkage and Durability Mechanics of Concrete and Concrete Structures